2015
DOI: 10.1111/bcp.12820
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic effects of mTOR inhibition in atherosclerosis

Abstract: Despite significant improvement in the management of atherosclerosis, this slowly progressing disease continues to affect countless patients around the world. Recently, the mechanistic target of rapamycin (mTOR) has been identified as a pre-eminent factor in the development of atherosclerosis. mTOR is a constitutively active kinase found in two different multiprotein complexes, mTORC1 and mTORC2. Pharmacological interventions with a class of macrolide immunosuppressive drugs, called rapalogs, have shown undeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 157 publications
(184 reference statements)
1
77
0
1
Order By: Relevance
“…Besides, multiple researchers have suggested that mTOR may offer new avenues in the regression of atherosclerotic plaques [36,37]. mTOR contributes in proliferation, lipogenesis, and energy metabolism possibly by targeting S6K and cyclin-dependent kinases (CDKs) [38]. Previous studies have evidenced that lncRNA UCA1 promoted malignant transformation and cancer progression through activation of mTOR pathway [14,39].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, multiple researchers have suggested that mTOR may offer new avenues in the regression of atherosclerotic plaques [36,37]. mTOR contributes in proliferation, lipogenesis, and energy metabolism possibly by targeting S6K and cyclin-dependent kinases (CDKs) [38]. Previous studies have evidenced that lncRNA UCA1 promoted malignant transformation and cancer progression through activation of mTOR pathway [14,39].…”
Section: Discussionmentioning
confidence: 99%
“…mTOR is a critical regulator of many fundamental features responding to upstream cellular signals and participating in the control of gene expression and cell behavior (33). Pharmacological intervention of mTORC1 with rapamycin has shown clear evidence of the value of mTOR inhibition in preventing the development of atherosclerosis and restenosis (34,35). Although mTORC1 has been linked to endothelial function and dysfunction, its downstream targets functioning in vascular dysregulation have not been examined in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced infiltration of macrophages into the vascular wall, with reduced secretion of inflammatory cytokines, was also observed in a rabbit model of atherogenesis . The effect on angiogenesis in one of these studies and in and in other experimental studies was associated with stimulation of the AMPK/inhibition of mTOR by metformin, which suggests that such a mechanism may be of relevance to the clinical therapeutic action of metformin. Other potentially vascular protective mechanisms described for metformin in experimental studies include reduced cholesterol uptake or enhanced cholesterol efflux from macrophages, inhibition of fission of mitochondria in endothelial cells, protection of mitochondrial function during and after myocardial ischaemia, and reduced formation of foam cells or neointima in the developing plaque.…”
Section: Cardiovascular Protection With Metforminmentioning
confidence: 99%